A rapid and visual dual LAMP-LFD assay for on-site simultaneous detection of influenza A virus (H1N1) and respiratory syncytial virus (RSV) - Zhang, Alang; Lan, Xingyu; Zhou, Hengxuan; Zhou, Ting; Xu, Zhihua; Cheng, Xinyu; Guo, Chenxi; Wei, Mingjie; Wu, Jiahui; Shi, Feng (Frontiers in Microbiology, 2025)
Respiratory tract infections caused by influenza A virus (IAV) and respiratory syncytial virus (RSV) are a major global health burden. To overcome the limitations of existing diagnostic techniques for timely detection (point-of-care testing), this study developed a dual rapid visual detection method based on loop-mediated isothermal amplification (LAMP) and lateral flow device (LFD) technologies for the simultaneous detection of H1N1 influenza virus and RSV. This method uses a dual-labeled probe system (H1N1: digoxigenin/biotin; RSV: 6-carboxyfluorescein/biotin) combined with a two-color latex microsphere signal system that enables the intuitive visual interpretation of multiple detection results. Compared with traditional nucleic acid detection, the entire detection process was completed within 40 min at a constant temperature of 63 °C and the operation was simple. After optimization, the method showed good sensitivity and specificity. The limit of detection for H1N1 IAV and RSV was as low as 7.78 × 103 copies/mL and 1.29 × 102 copies/mL, respectively, and no cross-reaction occurred with six common non-target pathogens. Clinical sample verification showed that the consistency between the detection and RT-qPCR results was 96.83%, which was significantly better than traditional antigen detection. The dual LAMP-LFD detection method established in this study provides an efficient solution for rapid on-site, synchronous, and visual screening in resource-limited environments and has important clinical application value.